KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN KINERJA KEUANGAN SEBAGAI PENENTU STRUKTUR MODAL PERUSAHAAN - Ida Maftukhah (Jurnal Dinamika Manajemen)
The objective of this research is to analyze the influence of managerial ownership, institutional ownership, asset growth, ROA, DPR, net sales, fixed asset ratio and corporate tax rate toward stock DER manufacturing company that listed on Indonesian Stock Exchange in the period of 2004-2008. Sample of this research consists of 10 manufacturing company. Purposive sampling methods were used as samples determining method. Data were provided by Indonesian Capital Market Directory (ICMD) for each company. Analysis technique that used in this research is multiple linier regression. The result of this research shows that Managerial ownership as dummy variable and ROA have a negative and significant influence toward DER. Asset growth and DPR have a positive and significant influence toward DER. Institutional ownership have a positive and significant influence toward DER. Otherwise net sales, fixed asset ratio and corporate tax rate have a positive and not significant influence toward DER. The result of this research shows that adjusted R2 is 33,4%